Estudo de nanocompósitos de pectina com nanopartículas de quitosana e carvacrol para aplicação em embalagens - Souza, Juliana Reghine (2017)
Brazilian researchers have performed out several works and developed several products from nanostructured materials, which has resulted in an expansion in its research. One of these research fields is focused on minimizing the environmental impact caused by petroleum-derived packaging, which has been increasingly used in our daily lives. From this context, food industries are facing several challenges of reducing environmental damage caused by synthetic polymers, being the production of biodegradable films produced from renewable sources one of the alternatives. Therefore, this project aimed to formulate pectin films with chitosan nanoparticles (CSNP) and carvacrol, the major substance of the oregano essential oil. The materials used were pectin (low methoxyl degree, MD), chitosan and carvacrol. The CSNP were synthesized by ionotropic gelatinization in the mass ratio 2:1 (chitosan/sodium triphosphate) and characterized by particle size distribution, zeta potential, infrared spectroscopy, thermal analyze, morphologies and antimicrobial activity. The mean size NPQS was close to 100 nm and Zeta potential above + 30 mV, indicating good suspension stability in water. The value of polydispersity index 0.5 indicates more homogeneous suspensions. The minimum inhibitory concentration (MIC) for chitosan was 0.15 mg/ml, whereas the NPQS values were 0.10 mg / ml. The films were produced by continuous casting and batch casting at the volumetric concentrations of 5% and 2% pectin in aqueous solution. They were characterized by thickness, infrared spectroscopy, mechanical and thermal properties, water vapor permeability, morphology and antimicrobial activity. The addition of NPQS in the 1% mass concentration of the pectin mass resulted in 100% increments in the mechanical properties. The presence of NPQS and carvacrol increased the second degradation temperature (TD) indicating that there may be a hydrogen interaction between chitosan and pectin. The barrier property remained unchanged with the addition of NPQS and carvacrol, and there could be competition between both reinforcing effects produced by NPQS and the plasticizer of carvacrol.